2020
DOI: 10.1021/acs.molpharmaceut.0c00517
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics and Physical Stability of Ibuprofen in Binary Mixtures with an Acetylated Derivative of Maltose

Abstract: In this paper, we explore the strategy increasingly used to improve the bioavailability of poorly water-soluble crystalline drugs by formulating their amorphous solid dispersions. We focus on the potential application of a low molecular weight excipient octaacetyl-maltose (acMAL) to prepare physically stable amorphous solid dispersions with ibuprofen (IBU) aimed at enhancing water solubility of the drug compared to that of its crystalline counterpart. We thoroughly investigate global and local molecular dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 77 publications
3
10
0
Order By: Relevance
“…They suggested that it could happen if the total energy of the interactions between the molecules of different species was lower than that between molecules of the same species. This hypothesis has been confirmed via DFT calculations in our previous investigations of amorphous binary mixtures containing CEL or IBU with the addition of acMAL [ 16 , 22 ].…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…They suggested that it could happen if the total energy of the interactions between the molecules of different species was lower than that between molecules of the same species. This hypothesis has been confirmed via DFT calculations in our previous investigations of amorphous binary mixtures containing CEL or IBU with the addition of acMAL [ 16 , 22 ].…”
Section: Resultssupporting
confidence: 66%
“…For many decades, it has been believed that the physical stability of drugs in both the supercooled and glass states is better if they are stronger materials, i.e., characterized by smaller values of the fragility parameter [ 13 , 36 , 37 , 38 , 39 , 40 ]. In the literature, there are known exceptions in the suggested correlation for both pure drugs and pharmaceutical compositions [ 2 , 5 , 10 , 22 , 41 , 42 , 43 ]. To verify the hypothesis in the case of the binary mixtures of ETB with acMAL, we calculated the values of m p by using Equations (4) and (5) and plotted the obtained results in Figure 8 c compared to those reported earlier for the CEL–acMAL mixtures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Predominantly, large molecular weight, massive conformational flexibility, uniform distribution of electronegative atoms, and hydrogen bonding are the factors favoring the existence of the glassy state, while molecular symmetry or aromaticity usually promote crystallinity [ 14 ]. Calorimetric and spectroscopic studies [ 15 ] as well as molecular-dynamics investigations [ 16 ] suggest that distinct trends of the vitrification tendency among similar chemicals can be traced to the strength of intermolecular interactions in bulk materials.…”
Section: Introductionmentioning
confidence: 99%
“…A first attempt to extrapolate the crystal growth kinetics using the augmentation of the approach by Genton and Kesselring introduced by Zhang et al, which links the natural logarithm of the rate constant for crystal growth to the water content in the ASD, has been presented in our previous study . Linking the crystal growth with the molecular mobility in glasses as published by Suryanarayanan et al, Greco et al, Paluch et al, and others, in this work, an approach is presented that correlates the crystal growth rate with the ratio of T g of the humid ASD and the storage temperature above T g . Although drug products are usually stored below T g and the glass physics is changed compared to the behavior above T g , this correlation allows us to give a worst-case estimation of crystal growth below T g , a sufficient approximation to determine ASD shelf life to ensure patient safety.…”
Section: Introductionmentioning
confidence: 90%